ANALISIS FAKTOR KESULITAN BELAJAR SISWA KELAS III DALAM MEMAHAMI MATERI STRUKTUR PEMERINTAHAN PENDIDIKAN PANCASILA DI SDN BANGKALAN - Husnul Khotimah; Saosa Yumrotus Sholikhah; Qurrotu Inayati Maula; Astien Diena Koesmini; Rukmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the internal factors that cause learning difficulties among third-grade students in understanding the topic of governmental structure in the subject of Civic Education at SDN Bangkalan. The research employed a qualitative approach with a case study method. The participants were third-grade students, and data were collected through classroom observation and in-depth interviews. The findings indicate that students’ learning difficulties are influenced by several internal factors, including: (1) limited cognitive development, as students are still at the concrete operational stage according to Piaget’s theory, making it difficult to comprehend abstract concepts of state power division; (2) low interest and learning motivation due to the perception that the material is boring and irrelevant to daily life; and (3) negative perceptions toward Civic Education, which is often associated with memorizing institutional terms rather than connecting to real-life experiences. These results highlight that internal factors play a crucial role in shaping students’ understanding of abstract material, thereby emphasizing the need for teaching strategies that align with the cognitive characteristics, interests, and perceptions of elementary school students.